The nature and origin of gold mineralization in the Tugela valley, Natal Structural and Metamorphic Province - De Klerk, Ian Duncan (Rhodes University, Faculty of Science, Department of Geology, 1991)
The project area is situated within the Tugela Valley, located in the Northern Marginal Zone of the Natal Structural and Metamorphic Province, and this work outlines the different styles of gold mineralization found in the Tugela Valley. Two different styles have been recognized and both have economic significance:- 1) Epigenetic shear zone-hosted gold occurs in late-stage relatively undeformed thin quartz veins confined to shear zones, and is present in both the greenschist facies Natal Thrust Belt and the amphibolite facies Natal Nappe Complex. However the vast majority of these occurrences are concentrated within the thrust front (i.e. the Natal Thrust Belt). The gold grades (up to 7 g/t) and the hydrothermal alteration assemblages associated with the epigenetic deposits have been documented. 2) An as yet unrecognized occurrence of syngenetic gold mineralization is found associated with the sediment-hosted exhalative massive, to semi-massive, sulphides of the iThuma prospect, located within the amphibolite facies Natal Nappe Complex. Here gold (up to 3 g/t) is concentrated together with the main sulphide are, as well as some gold enrichment (230ppb) in the hydrothermally altered footwall feeder pipe. It is proposed that the epigenetic mineralization was formed as a consequence of the northward directed abduction of the major thrust slices of the Natal Nappe Complex. This increased the permeability of the rocks and provided channelways for the focussing of fluids. Deposition took place at the thrust front where metamorphic hydrothermal fluids interacted with meteoric water.
Keywords: Gold ores -- Geology -- South Africa; Gold mines and mining -- South Africa